Retracted Article | E-Perelek: Penguatan Pangan Melalui Inovasi Kebijakan Berbasis Modal Sosial dan Teknologi di Kabupaten Purwakarta, Jawa Barat - Kintansari Adhyna Putri; Ichlasul Amal (Universitas Trunojoyo Madura, 2019)
As a country that is rich in local wisdom, the Indonesian people know the tradition of 'Mutual Cooperation'. One of the traditions of mutual cooperation is Perelek, which is the activity of the West Java Sundanese farmers who distribute rice yields to fellow marginal farmers and marginalized groups. The Perelek tradition was adopted and developed into the Smart Regency policy of Purwakarta Regency named Automated Teller Machine Rice (E-Perelek). Changing conditioning relations 'mutual cooperation' is moderated by technology input as well as the implementation of the Electronic Government (E-gov) paradigm. E-Perelek is claimed to be able to foster a sense of solidarity while increasing the availability of rice for food for the poor in Purwakarta with better quality than poor rice (Raskin). This condition is in line with the 2nd objective of the Sustainable Development Goals (SDGs) in ending hunger, achieving food security and improving nutrition, and promoting sustainable agriculture. The methodology used in this paper is a qualitative approach with descriptive analysis. This paper aims to critically analyze the implications of the change in Perelek's tradition to be an eager policy on food security for small communities in Purwakarta.Notice of Article RetractionReports the retraction of